Kajian Pengaruh Kemiringan Jalan Angkut Terhadap Konsumsi Penggunaan Bahan Bakar Truck Pada Produksi Batubara Di Pit Barat Pt.Aic Jaya Kec.Talawi Sawahlunto Sumatera Barat - Rian Saputra; Dedi Yulhendra (Departemen Teknik Pertambangan FT UNP, 2021)
Abstract. Sawahlunto City is one of the areas that has very potential coal resources in West Sumatra and is very interesting to work on. PT. Allied Indo Coal Jaya is a company engaged in coal mining located in Parambah, Talawi District, Sawahlunto City, West Sumatra. PT.Allied Indo Coal Jaya carries out coal mining with underground and open pit mining systems. Coal mining with an open pit system includes land clearing, stripping of topsoil, removing topsoil for disposal, loading and transporting coal to stockpiles. . In the topsoil and coal acreage activities requiring mechanical devices, one of the mechanical devices used is the Hino FM 260 JD dump truck and the Caterpillar 320 D excavator. The use of transportation equipment as the main equipment in mining operations cannot run without fuel. High fuel prices can affect mining operating costs. Factors that influence the increase in fuel consumption are the slope, the distance traveled and the load. PT AIC is successful in planning the slope of the haul road with a grade of 9%, it turns out that in the field there are many haul road slopes obtained by researchers of more than 10%. Incorrect road slopes can affect fuel consumption, cycle time and conveyance productivity so that it can affect production.Keywords: Sawahlunto, Fuel Consumption, Coal Mining, Slope.